THE URGENCY OF EVALUATE ISLAMIC EDUCATION IN A 21st CENTURY PERSPECTIVE - Moh. Faizin; Nailal Himmah Attaroqiya; Linda Dwi Aryanti (Universitas Dharmawangsa, 2022)
The purpose of evaluating islmaic education is to monitor the educational process. In this context, the goal of combining Islamic values with Islamic education and Islamic law must remain one of the highest goals of Islamic education. When it comes to making the core of the Islamic education process, the evaluation must be clear and comprehensible. This is important because the level of knowledgepf students is based on the assessment of Islamic education. Not only that, education has a great role in students to understand Islmaic education and some of the problems that students bring. According to the meaning of evaluation, he tried the level of success and failure in the process of Islamic education, including all it’s aspects and objectives. Several principles, methods and procedures should be followed when evaluating to achieve the best result. By conducting an evaluation of the learning outcomes test, the test will be examined so that from the results it can be seen which components of the teaching and learning process are still weak.